BILANGAN INVERS DOMINASI TOTAL PADA GRAF BUNGA DAN GRAF TRAMPOLIN - Febby Desy Lia; Nilamsari Kusumastuti; Fransiskus Fran (Mathematics Study Program, Faculty of Mathematics and Natural Sciences, Lambung Mangkurat, 2022)
Given a simple, finite, undirected and contains no isolated vertices graph , with is the set of vertices in and is the set of edges in . The set is called the dominating set in if for every vertex of is adjacent to at least one vertex in . The set is called the total dominating set in graph if for every vertex in is adjacent to at least one vertices in . If is the total domination set with minimum cardinality of the graph and contains another total domination set, for example , then is called the inverse set of total domination respect to . The minimum cardinality of an inverse set of total domination is called the inverse of total domination number which is denoted by .The set of domination and total domination is not singular. A graph that has a total domination set does not necessarily have a inverse total domination set. In this study, exact values are found of , and and,, n is even and , where be a flower graph and T<span style='font-size:10.0pt;mso-ansi-font-siz